The Connection of Klenteng Talang with Tan Eng Hoat and Tan Sam Tjai and Its Role in the History of the Cirebon Kingdom in Chinese Records - Nugrahanto, Widyo; Sofianto, Kunto; Koeshandoyo, Eko Wahyu; Septiani, Ayu (Department of Anthropology, Faculty of Social and Political Sciences, Hasanuddin University., 2024)
Many people's ignore two Chinese Muslim figures (Tan Eng Hoat and Tan Sam Tjai) and their relationship with the Klenteng Talang is because there are not many local ancient texts that contain them or tell about them. The only text that contains the existence of these two figures and their relationship with the Klenteng Talang is the Klenteng Talang China News. To be able to reveal again the two figures mentioned above and the Klenteng Talang, we need to look again at the Chinese news about the Klenteng Talang, Cirebon. This research aims to re-reveal the role of Tan Eng Hoat and Tan Sam Tjai in the history of the Cirebon Kingdom based on the Chinese news of Klenteng Talang and its current relationship with the Chinese temple in Cirebon. Using intertextual approach with historical method was used in four stages of work, namely heuristic, criticism, interpretation, and historiography to the writings of the Chinese News text of Klenteng Talang. Our informants consists of care takers of Klenteng Talang and official of Harbourmaster and Port Authority Office in Muara Jati. The findings indicate that there is an influence of Chinese Muslims in the history of Cirebon, one of the archaeological remains of which is the Klenteng Talang building in Cirebon. Klenteng Talang, Tan Eng Hoat, and Tan Sam Tjai had a very close relationship in the history of the Cirebon Kingdom in the Chinese news about the Chinese Temple. Although Tan Eng Hoat and Tan Sam Tjai were Muslims who converted to Confucianism, their relationship with Klenteng Talang cannot be ignored. Tan Eng Hoat played a significant role in the early establishment of the Cirebon Kingdom. Even the idea of establishing the Cirebon Kingdom came from Tan Eng Hoat, who conveyed it to Sunan Gunung Jati. Tan Sam Tjai, who was younger than Tan Eng Hoat, also played a significant role in helping to finance the Islamic kingdom of Cirebon until the end of his life, in spite of the fact he left Islam.